The Challenge of Leadership in Higher Education in An Age of Disruption - Stephen Murgatroyd (Journal of Ethics in Higher Education)
This paper explores the challenging role of leadership in higher education. It seeks to understand the challenges faced at a time of volatility and uncertainty, especially given the financial and operational challenges faced by higher education systems around the world. It suggests that there are five major challenges for our understanding of leadership in this sector: (a) leadership is reactive rather than anticipatory; (b) higher education has been captured by neo-liberal new public management; (c) leadership lacks the courage to be inspirational and innovative; (d) that “business as usual” is no longer a viable strategy, especially given changes in the nature of academic work; and (e) leaders show a failure of imagination. The paper suggests that it is time to seek a new understanding of what a higher education institution is and that this will require a new kind of leader for a new age.